Speaking 3’S: Innovative of Contextual Method in English Language Teaching for Speaking - Hassan, Muhammad; Hafizah (LPPM STKIP AL MAKSUM, 2023)
English as an international language, it is a key to conquer the world. Education is a tool that enables students to gain knowledge and develop their creative thinking abilities. The aim of this research is to evaluate the advantages of implementing SPEAKING 3’S, an innovative method for English Language English language teaching, especially in speaking. Within the confines of a quantitative descriptive research design, an experimental group and a control group were compared. In the experimental group, two weeks of English classes were modified within the framework of SPEAKING 3’S, an innovative and newest English language teaching style. In the control group, there is no instructional activities based on the SPEAKING 3’S technique were implemented. Pre and post-tests were administered to evaluate the efficacy of the SPEAKING 3’S method on the speaking skills of students and to compare the experimental and control groups. In addition, observations were done to evaluate the participants in both courses and compare their similarities and differences (students' interactions with the teacher and their opinions on the English language teaching style implication). The adoption of the SPEAKING 3’S technique in English lessons improves students' speaking skills and can assist offer an original point of view to English Language teaching, according to the findings of this research. Keywords : SPEAKING 3’S, speaking, method